Riesgo de muerte por insuficiencia cardiaca congestiva en pacientes anémicos de la población peruana - Guevara Tirado, Alberto (2023)
Objective: To determine the risk of death from underlying congestive heart failure among Peruvian patients with anemia. Materials and methods: An observational, descriptive, case-control and retrospective study based on data from theSistema Informático Nacional de Defunciones (SINADEF - National Death Computer System) of the Ministry of Health of Peru (MINSA) and conducted between January 2021 and August 2022. A non-probability purposive convenience sampling wasused considering the inclusion and exclusion criteria. All patients with and without anemia who died from congestive heart failure or other comorbidities were included in the research, totaling 35,724 people. The variables were anemia, defined as a condition related to the amount or number of red blood cells and hemoglobin, as well as to iron absorption and availability, and congestive heart failure, defined as the inability of the myocardium to pump blood efficiently. Chi-square test and phi and Cramer’s V coefficients were used to determine the presence and degree of association of the variables and the odds ratio for risk estimation. A significant p value less than 0.05 with a 95 % confidence interval was considered. Results: Anemia was moderately associated with congestive heart failure: 62.80 % of people with anemia died from this disease.The variables were statistically related and, according to phi and Cramer’s V coefficients, there was a moderate relationship. People with anemia had 11.14 times higher risk of dying from congestive heart failure than people with other comorbidities.